Nuclease Stn alpha from Streptomyces thermonitrificans: characterization of the associated adenylic acid preferential ribonuclease activity - Deshmukh, Satej S. (Current Microbiology, 2007)
Nuclease Stn alpha from Streptomyces thermonitrificans hydrolyses DNA and RNA at the rate of approximately 10:l. The optimum pH and temperature for RNA hydrolysis were 7.0 and 45 degrees C. The RNase activity of nuclease Stn alpha had neither an obligate requirement of metal ions nor was it activated in the presence of metal ions. The enzyme was inhibited by Zn2+, Mg2+, Co2+, and Ca2+; inorganic phosphate; pyrophosphate; NaCl; KCl; and metal chelators. It was stable at high concentrations of urea but susceptible to low concentrations of Sodium dodecyl sulfate and guanidine hydrochloride. The rates by which nuclease Stn alpha hydrolysed polyribonucleotides occurs in the order of poly A >> RNA >> poly U > poly G > poly C. The enzyme cleaved RNA to 3' mononucleotides with preferential liberation of 3'AMP, indicating it to be an adenylic acid preferential endonuclease.